2D Focusing of Reﬂected Hard X-rays and Thermal Neutron Beams in the Presence of External Temperature Gradient; Radiation from Relativistic Electrons in Periodic Structures (RREPS-19) - Kocharyan V. R. Vagan Rashidovich; Movsisyan A. E.; Gogolev A. S. Aleksey Sergeevich; Mkrtchyan A. R. Alpik Rafaelovich (Applications of Monochromatic X-ray, [gamma]-ray, 2019)
Title screen